Corrosion‐resistant and friction‐reducing performance of super‐hydrophobic coating on hot‐dip galvanised steel in a 3.5% NaCl solution. (23rd June 2021) - Cao, Lei; Wan, Yong; Li, Yang; Yang, Shuyan
Abstract: Corrosion‐resistant and tribological performance of hot‐dipped galvanised steel (HDGS) in highly aggressive coastal and marine environments needs improvement. In this paper, the super‐hydrophobic coating with a contact angle of 150° and a sliding angle of <10° is fabricated on HDGS by a simple method that includes self‐assembly of stearic acid on oxidised HDGS. SEM and XRD are used to characterise the morphology and phase structure of the oxidised HDGS, respectively. Infrared microscopy is used to investigate the chemical bonding mode of stearic acid on the oxidised HDGS. It is found that super‐hydrophobic coating provides effective corrosion resistance for HDGS in a 3.5% NaCl solution. It also shows a lower friction coefficient with wear protection in a 3.5% NaCl solution, as compared with the bare HDGS.